2014
DOI: 10.1021/jo5015195
|View full text |Cite
|
Sign up to set email alerts
|

Conception and Evolution of Stereocontrolled Strategies toward Functionalized 8-Aryloctanoic Acids Related to the Total Synthesis of Aliskiren

Abstract: A detailed account is given describing the approaches used toward the total synthesis of aliskiren. In particular, ring-closing metathesis with the Hoveyda-Grubbs catalyst accelerates the formation of a 9-membered lactone from an (R)-ester. The diastereomeric (S)-ester leads to the formation of dimeric dilactones, which were characterized by X-ray analysis and chemical conversions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…[36][37][38] The exclusive selectivity for 8 can be rationally understood and explained by looking at proposed conformation of oxonium intermediate 9, in which the least hindered approach of the nucleophile led to the important C1, C10 trans configuration of 8. Conversion of 8 to Ambrox ® -like 39 compound 10 was achieved through a ruthenium-catalyzed ring-closing olefin metathesis (RCM) in the presence of 10 mol% ruthenium catalyst at 10 mmol L −1 in dry and degassed, refluxing dichloromethane for 24 h, 40,41 and deacetylation of compound 8 with potassium carbonate gave alcohol 11 in a high yield (85%). Alternatively, the tricyclic lactone molecular scaffold could undergo a variety of further manipulations as a result of the cyclic olefin, such as oxidation, epoxidation, halogenation, and cross-coupling, to afford more complex compounds.…”
Section: Chemistrymentioning
confidence: 99%
“…[36][37][38] The exclusive selectivity for 8 can be rationally understood and explained by looking at proposed conformation of oxonium intermediate 9, in which the least hindered approach of the nucleophile led to the important C1, C10 trans configuration of 8. Conversion of 8 to Ambrox ® -like 39 compound 10 was achieved through a ruthenium-catalyzed ring-closing olefin metathesis (RCM) in the presence of 10 mol% ruthenium catalyst at 10 mmol L −1 in dry and degassed, refluxing dichloromethane for 24 h, 40,41 and deacetylation of compound 8 with potassium carbonate gave alcohol 11 in a high yield (85%). Alternatively, the tricyclic lactone molecular scaffold could undergo a variety of further manipulations as a result of the cyclic olefin, such as oxidation, epoxidation, halogenation, and cross-coupling, to afford more complex compounds.…”
Section: Chemistrymentioning
confidence: 99%
“…The structure of the C 2 -symmetrical dilactone 6 was ascertained by X-ray crystallography (Scheme 2). 14 In view of the continuing interest to develop viable synthetic routes to aliskiren, we focused on the key ring-closing metathesis step in our original synthesis. 7 In this paper, we report our qualitative observations pertaining to the reaction of the p-methoxyphenyl analogues 1b and 3b as well as their mono-and disubstituted diastereomeric esters in the presence of a variety of catalysts, in order to determine the influence of the isopropyl and vicinal aryl substituents and their relative stereochemistry on the nature of the products (Figure 1).…”
Section: Syn Thesismentioning
confidence: 99%
“…We then returned to the original disubstituted model (S,R,S)-ester 1b, and studied the reaction in the presence of G2 and then H-G2 catalysts and the newer generation catalysts ( Figure 1). 16 Using 5 mol% catalyst in refluxing toluene led to the nine-membered lactone 2b in good yield, al-though the reaction was 2-3 times slower with the new generation catalysts (entries [13][14][15][16][17]. Finally, the (S,S,S)-ester 3b was subjected to the same reactions conditions, leading solely to the dilactones 5 and 6 as previously observed with the G2 and H-G2 catalysts (entries 18-22).…”
Section: Syn Thesismentioning
confidence: 99%
“…Starting from the first Novartis–Speedel synthesis, several research groups, from both academia and industry, have reported brilliant solutions to the problem of aliskiren synthesis. …”
Section: Introductionmentioning
confidence: 96%